Integração de centrais geradoras hidrelétricas em ponte-barragem multiuso na Amazônia rural - PORTILHO, Vitória Barbosa (2024)
Even with the growth of recent years, the supply of electricity in rural Amazonia is still a major problem, due to the difficulty of accessing communities, the high cost of transmitting and distributing energy to small populations. In addition, the road network crosses several small watercourses, with access restricted to small wooden bridges, which hinders the logistics of transporting agricultural production from existing communities. To meet this energy demand, the small-scale supply model, mainly with the implementation of hydroelectric generating stations (HGC), has proved to be a good alternative. This paper presents a methodology that aims to replace wooden bridges with a concrete bridge/dam, including a HGC integrated into the bridge structure. The proposed methodology begins with a hydrological study, analyzing the permanence curve and the key curve. In order to choose the plant's operational arrangement and its energy aspects, and to determine the size of the machines, the hydraulic turbines (HT) were parameterized and similarized using an existing machine from the literature. Finally, the methodology was applied to a community with energy demand from an agro-industry. Two propeller-type hydraulic turbines were parameterized with the number and size defined based on a local hydrological study, along with the turbine's efficiency, to meet the demand of the community where it will be installed. The proposed scheme was able to generate 47,244.94 kWh/year, meeting the project's demand, which was estimated at 41,045.36 kWh/year. This same methodology has the potential to be successfully applied in various areas of the Amazon region and similar, where there is a low drop and flow variation.